Targeting dormant tuberculosis bacilli: results for molecules with a novel pyrimidone scaffold - Joshi, Rohit R.; Barchha, Avinash; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Sarkar, Sampa; Sarkar, Dhiman; Joshi, Rohini R.; Joshi, Ramesh A.; Shah, Anamik K.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2015)
Our inability to completely control TB has been due in part to the presence of dormant mycobacteria. This also renders drug regimens ineffective and is the prime cause of the appearance of drug-resistant strains. In continuation of our efforts to develop novel antitubercular agents that especially target dormant mycobacteria, a set of 55 new compounds belonging to the pyrimidone class were designed on the basis of CoMFA and CoMSIA studies, and these were synthesized and subsequently tested against both the dormant and virulent BCG strain of M.tuberculosis. Some novel compounds have been identified which selectively inhibit the dormant tuberculosis bacilli with significantly low IC50 values. This study reports the second molecule after TMC-207, having the ability to inhibit tuberculosis bacilli exclusively in its dormant phase. The synthesis was accomplished by a modified multicomponent Biginelli reaction. A classification model was generated using the binary QSAR approach - recursive partitioning (RP) to identify structural characteristics related to the activity. Physicochemical, structural, topological, connectivity indices, and E-state key descriptors were used for generation of the decision tree. The decision tree could provide insights into structure-activity relationships that will guide the design of more potent inhibitors.
Keywords: Antitubercular activity; dormant tuberculosis bacilli; pyrimidones; recursive partitioning

Two chitotriose-specific lectins show anti-angiogenesis, induces caspase-9-mediated apoptosis and early arrest of pancreatic tumor cell cycle - Singh, Ruby; Nawale, Laxman; Sarkar, Dhiman; Suresh, C. G. (Plos One, 2016)
The antiproliferative activity of two chito-specific agglutinins purified from Benincasa hispida (BhL) and Datura innoxia (DiL9) of different plant family origin was investigated on various cancer cell lines. Both lectins showed chitotriose specificity, by inhibiting lectin hemagglutinating activity. On further studies, it was revealed that these agglutinins caused remarkable concentration-dependent antiproliferative effect on human pancreatic cancerous cells but not on the normal human umbilical vein endothelial cells even at higher doses determined using MTT assay. The GI(50) values were approximately 8.4 mu g ml(-1) (0.247 mu M) and 142 mu g ml(-1) (14.8 mu M) for BhL and DiL9, respectively, against PANC-1 cells. The growth inhibitory effect of these lectins on pancreatic cancer cells were shown to be a consequence of lectin cell surface binding and triggering G(0)/G(1) arrest, mitochondrial membrane depolarization, sustained increase of the intracellular calcium release and the apoptotic signal is amplified by activation of caspases executing cell death. Interestingly, these lectins also showed anti-angiogenic activity by disrupting the endothelial tubulogenesis. Therefore, we report for the first time two chito-specific lectins specifically binding to tumor glycans; they can be considered to be a class of molecules with antitumor activity against pancreatic cancer cells mediated through caspase dependent mitochondrial apoptotic pathway.

Triazole-diindolylmethane conjugates as new antitubercular agents: synthesis, bioevaluation, and molecular docking - Danne, Ashruba B.; Choudhari, Amit S.; Chakraborty, Shakti; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (MedChemComm, 2018)
We describe the synthesis of novel triazole-incorporated diindolylmethanes (DIMs) using a molecular hybridization approach. The in vitro antitubercular activity of the DIMs against Mycobacterium tuberculosis H37Ra (ATCC 25177) was tested in the active and dormant state. Among all the synthesized conjugates, the compounds 6b, 6f, 6l, 6n, 6q, 6r, and 6s displayed good antitubercular activity against both the active and dormant Mtb H37Ra strain. The compound 6l exhibited good antitubercular activity against dormant Mtb H37Ra with an IC50 value of 1 g mL(-1) and IC90 (MIC) value of 3 g mL(-1). The compounds 6b, 6l, and 6r displayed good antitubercular activity against active Mtb H37Ra with IC50 values of 2.19, 1.52, and 0.22 g mL(-1), respectively. The compounds 6b, 6h, 6l, and 6s displayed more than 70% inhibition against the Gram-positive Bacillus subtilus strain at 3 g mL(-1). The molecular docking study showed the binding modes of the titled compounds in the active site of the DprE1 enzyme and assisted with elucidating a structural basis for the inhibition of Mycobacteria.

Thiazolyl-pyrazole derivatives as potential antimycobacterial agents - Takate, Sushma J.; Shinde, Abhijit D.; Karale, Bhausaheb K.; Akolkar, Hemant; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (Bioorganic & Medicinal Chemistry Letters, 2019)
Mycobacterium tuberculosis (Mtb) is an obligate aerobe that is capable of long-term persistence under conditions of low oxygen tension. A series of thiazolyl-pyrazole derivatives (6a-f, 7a-f, 8c, 8e) were screened for antimycobacterial activity against dormant M. tuberculosis H37Ra (D-MTB) and M. bovis BCG (D-BCG). Nine thiazolyl- pyrazole analogs, 6c, 6e, 7a, 7b, 7c, 7e, 7f, 8c and 8e exhibited promissing minimum inhibitory concentration (MIC) values (0.20-28.25 mu g/mL) against D-MTB and D-BCG strains of Mtb. Importantly, six compounds (7a, 7b, 7e, 7f, 8c and 8e) exhibited excellent antimycobacterial activity and low cytotoxicity at the maximum evaluated concentration of > 250 mu g/mL. Finally, the promising antimycobacterial activity and lower cytotoxicity profile suggested that, these compounds could be further subjected for optimization and development as a lead, which could have the potential to treat tuberculosis.
Keywords: antimycobacterial activity; Cytotoxicity; Pyrazole; thiazoles

Tetrazoloquinoline-1,2,3-triazole derivatives as antimicrobial agents: synthesis, biological evaluation and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Akolkar, Satish V.; Nagargoje, Amol A.; Khedkar, Vijay M.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
In search of new active molecules, a small focused library of tetrazoloquinoline-based 1,2,3-triazoles has been efficiently preparedviaclick chemistry approach. Several derivatives were found to be exhibiting promising antimicrobial and antioxidant activity characterized by their lower minimum inhibitory concentration values. All the synthesized compounds exhibited excellent antibacterial activity against Gram negative bacteriaE. coliandF. devoransand antifungal activity againstC. albicansandA. niger. Further, these compounds were tested for their antitubercular activity against dormantMTB H37Raand dormantM. bovis BCGusing XRMA assay protocol and showed no significant activity. Also, the synthesized compounds were found to have potential antioxidant activity with IC(50)range = 12.48-50.20 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against the active site of fungalC. albicansenzyme P450 cytochrome lanosterol 14 alpha-demethylase, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of thein vitroandin silicostudy suggest that the triazole-incorporated tetrazoloquinolines may possess the ideal structural requirements for further development of novel therapeutic agents.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Docking study

Two antibacterial spiro compounds from the roots of Artemisia pallens wall: evidence from molecular docking - Honmore, Varsha S.; Natu, Arun D.; Khedkar, Vijay M.; Arkile, Manisha A.; Sarkar, Dhiman; Rojatkar, Supada R. (Natural Product Research, 2022)
Bioassay-guided isolation from acetone extract of the roots of Artemisia pallens Wall yielded two spiro compounds (1 and 2). The structures of these compounds were determined on the basis of spectroscopic techniques such as IR, MS, 1 D and 2 D- NMR. The acetone extract, fractions and the isolated two compounds were investigated for their antibacterial activity against two gram negative (E. coli, P. aeruginosa) and two gram positive (S. aureus, B. subtilis) bacterial strains. Compound (2) showed the best spectra of activity with IC50 and MIC values between 2.48-3.08 and 12.78 - 21.77 mu M and Compound (1) with 2.57-3.69 and 38.17 - 80.57 mu M, respectively, for the four bacterial strains, whereas inactive against Mycobacterium tuberculosis. Molecular docking study could further help in understanding the various interactions between these compounds and DNA gyrase active site in detail and thereby could provide valuable insight into the mechanism of action.
Keywords: antibacterial activity; antimycobacterial activity; Artemisia pallens; Asteraceae; Molecular docking; spiro compound

Total synthesis, structure elucidation and expanded bioactivity of icosalide A: effect of lipophilicity and ester to amide substitution on its bioactivity - Dangi, Abha; Pande, Bharat; Agrawal, Sonia; Sarkar, Dhiman; Vamkudoth, Koteswara Rao; Marelli, Udaya Kiran (Organic & Biomolecular Chemistry, 2023)
The first total synthesis of icosalide A, an antibacterial depsipeptide that is unique in that it contains two lipophilic beta-hydroxy acids, has been achieved by following Fmoc solid-phase peptide synthesis in combination with solution-phase synthesis. The ambiguity in the absolute stereochemistry of icosalide A has been resolved by synthesizing the reported structures and other relevant diastereomers of icosalides and comparing their NMR data. NMR-based structure elucidation of icosalide A revealed a well-folded structure with cross-strand hydrogen bonds similar to the anti-parallel beta-sheet conformation in peptides and displayed a synergistic juxtaposition of the aliphatic sidechains. 12 analogues of icosalide A were synthesized by varying the constituent lipophilic beta-hydroxy acid residues, and their biological activities against Bacillus thuringiensis and Paenibacillus dendritiformis were explored. Most of these icosalide analogues showed an MIC of 12.5 & mu;g mL(-1) against both bacteria. Swarming inhibition by icosalides was least in B. thuringiensis (8.3%) compared to that in P. dendritiformis (33%). Furthermore, this is the first report of icosalides showing assured inhibitory action (MIC between 2 and 10 & mu;g mL(-1)) against the active stage of Mycobacterium tuberculosis and cancer cell lines such as HeLa and ThP1. This study could help optimize icosalides for anti-TB, antibacterial, and anti-cancer activities.